Alport's syndrome. Issue 4 (April 1997) - Flinter, F
Abstract : Alport's syndrome (AS) is a progressive glomerulonephritis which is associated with high tone sensorineural deafness and characteristic eye signs. It accounts for 0.6% of all patients who start renal replacement therapy in Europe, and is most commonly inherited as an X linked disorder with a gene frequency of 1 in 5000. During the last six years several type IV collagen genes have been implicated in the aetiology of AS, and mutation detection studies are enabling genotype/phenotype correlations to be made, as well as facilitating carrier detection and prenatal diagnosis.